Evaluasi Efektivitas Web Portal Dengan Pendekatan Utility System (Studi Kasus: Universitas Muhammadiyah Purworejo) - Singgih Arif Widodo; Wahju Tjahjo Saputro (Universitas Muhammadiyah Purworejo, 2018)
This research aimed to evaluate portal web University Muhammadiyah Purworejo by using utili-ty system approach. Utility system approach to evaluate portal web from the point of the system effectiveness, firstly proposed by Kendall. This approach captured the perception of the system based on 6 points of view, which are possession, form, place, time, actualization and goal, as well as the scale of measurement using a likert scale and SPSS software. This study uses a re-search instruments with a likert scale questionnaire. The results showed how good the quality of the portal web University Muhammadiyah Purworejo, and any item of utility system that con-tributed the most to improving the quality of the system, as well as proposals that may be submit-ted to the management of portal web to develop more qualified information system.